Deadly papaya disease - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
In Guadeloupe and Martinique a bacteriological infection is killing both local and recently introduced varieties of papaya. Chemical control has so far been of little use against this vascular bacterium. At present the only effective measure to...